Inclined Lorentz force impact on convective-radiative heat exchange of micropolar nanofluid inside a porous enclosure with tilted elliptical heater - Yan, Shu-Rong; Izadi, Mohsen; Sheremet, Mikhail A.; Pop, Ioan; Öztop, Hakan Fehmi; Afrand, Masoud (Pergamon-Elsevier Science Ltd, 2020)
The combined impacts of inclined Lorentz force and thermal radiation on natural convection inside a porous chamber having micropolar nanoliquid and elliptical tilted heater are examined numerically. Micropolar fluid containing nanoparticles of copper oxide of low concentration circulates within the domain affected by the buoyancy and Lorentz forces. KKL approach is applied to define dependency of the nanofluid heat conductivity and viscosity on the nano-sized particles concentration and temperature, simultaneously. Governing equations with relevant boundary conditions written in non-dimensional stream function were solved by the Galerkin finite element method. An impact of important control parameters on micropolar nanofluid flow and heat exchange was analyzed. It was shown that change of the elliptical heater orientation reflects a significant modification of considered isolines and heat exchange rate. At the same time, average Nusselt number has maximum values for alpha = 0 and alpha = pi and minimum value at alpha = pi/2.
Keywords: MHD natural convection; Micropolar nanofluid; Porous enclosure; Internal elliptic heated element